Influence of cryoprotectors on the viability of cryopreserved carob tree immature pollen - Custódio, L; Romano, Anabela (MTT, 2008)
In this work the viability of carob tree (Ceratonia siliqua L.) cryopreserved immature pollen was evaluated after 5 and 8 months of storage. Anthers isolated from male and hermaphrodite flowers at developmental stages I and II with microspores at the late uninucleate to early binucleate stage, were cryopreserved by using ultra-rapid cooling method. Different types of cryoprotectants at different concentrations were used, namely carbohydrates (sorbitol: 0.5 M, 1 M, and 2 M; mannitol: 0.5 M and 1 M; sucrose: 0.5 M, 1 M and 2 M; glucose: 0.5 M, 1 M and 2 M; and other chemical substances (dimethylsulfoxide - DMSO: 3.5, 5, 7 and 10%, v/v; glycerol: 5, 10 and 15%, v/v; glycerol + DMSO: 2.5% + 2.5%, 1% + 5% and 5% + 5%, v/v; proline: 10%, v/v; ethyleneglycol: 2.5%, v/v and poliethyleneglycol: 10%, v/v. Anthers were pretreated by the addition of 10 ml of the cryoprotective solution to test tubes containing the anthers, divided in 4 applications of 2.5 ml, at 5 min intervals. The test tubes were maintained 24 h in a roller, at 25 rpm at RT. The anthers were then dehydrated by addition of 1 ml of the cryoprotective solution to each tube, divided in 4 applications of 0.25 ml, at 5 min intervals. After 20 min, the tubes were plunged to LN for 1 h, and stored at 80 ºC. In other assay, the anthers were cryopreserved without the addition of the cryoprotective solution. After storage, the samples were rewarmed in a 40 ºC water bath for 15 min, the cryoprotectant solution was drained off and the viability of pollen was evaluated by using the fluoresceine diacetate (FDA) test. Regardless of the type of cryoprotectant used both the application of the cryoprotectants and their presence during the period of storage generally promoted pollen viability compared with the control. The anthers excised from flowers at developmental stage I were more suitable for cryopreservation. When carbohydrates were used as cryoprotectants, pollen viability was not significantly affected by the developmental stage of the flowers from which the anthers were taken, and the most effective treatment consisted of a pretreatment with 0.5 M sucrose and a storage period of 5 months (~60% of viability). When DMSO was used as cyoprotectant pollen viability was affected not only by flower developmental stage but also by the sexual type of the donor plant, with the best results observed with anthers taken from hermaphrodite flowers at stage I. When using other chemical substances, it was observed that the use of solutions containing two different cryoprotectants were more effective than cryoprotectants alone. The best results were obtained with glycerol (2.5%) + DMSO (2.5%) (88% of viability). When using carbohydrates as cryoprotectants, the maximum percentage of viability obtained was lower than that observed with the application of other chemical substances. Although there is a need to increase the viability levels and to evaluate the response of cryopreserved microspores to induction of androgenesis, these results show that the cryopreservation of immature pollen of carob tree is possible, by using a relatively simple technique and maintaining high viability.
Keywords: Ka; Ceratonia siliqua; sorbitol; mannitol; sucrose; glucose; dimethylsulfoxide; glycerol; proline; ethyleneglycol; poliethyleneglycol